PERJANJIAN KONSINYASI ANTARA DISTRO DENGAN SUPPLIER DALAM PRAKTEK DI KOTA DENPASAR - Ngurah Wardiyana, Kadek; Supasti Darmawan, Ni Ketut; Wiratni Darmadi, A. A. Sagung (Kertha Semaya : Journal Ilmu Hukum, 2014)
The background inthis paper isthe rapid development of businessin Indonesia,along with the advancement of technology and the available of internet, whichmake business become unlimited developed, especially in Denpasar city,characterized by the development of consignment agreement or agreementbetween the two companies in which the supplier company will send goods to thedistributor outlet for sale. This agreement isthe development of a new agreementand occurs because society and business actors are needed to take part togetherin business. This paper, therefore, aimsto determine the form of consignmentagreement between distributors and suppliers,and to find out the legal systemtaken by supplier in case of default distributor, furthermore, this paper usedempirical research, that is,the application of the Third Books of Civil Law whichdiscusses the issues of agreement or contract. The conclusion on this issue is theconsignment agreement between distributions with suppliers is a consignmentcontract or agreement entrusted the selling and remedies for distributions madeby the supplier in default liable to pay damages in flicted experienced supplier.
Keywords: Agreement Consignment, Supplier, Distributor, Market